The art of letting go: Transforming participatory research on adaptation practices among local livestock-keepers in East Africa in times of Covid-19 - Habermann, Birgit; Crane, Todd A.; Gichuki, Leah; Worku, Tigist; Mugumya, Roland; Maiyo, Nathan; Kiptoo, E.; Goshme, Shenkute; Mohammednur, F.; Tugume, G.; Satia, K.A.; Siamito, J.R. (Frontiers Media, 2022)
Participatory action research (PAR) puts high emphasis on the interaction of the research participants. However, with the onset of the Covid-19 pandemic in March 2020, the central role of researchers in participatory research processes had to be questioned and revisited. New modes of PAR developed dynamically under the new circumstances created by the pandemic. To better understand how Covid-19 changed the way PAR is applied, we analyzed PAR in agricultural research for development carried out in the Programme for Climate-Smart Livestock Systems (PCSL) implemented by the International Livestock Research Institute (ILRI) at five research sites in Kenya, Ethiopia, and Uganda. To understand how PAR changed in a component on adaptation research in the PCSL we facilitated a reflexive study with livestock keepers and researchers to document their experiences of PAR during the Covid-19 pandemic. The analytical framework focuses on highlighting the core characteristics and the underlying ethos of PAR in this case study. The lessons learnt in the process of adapting to the realities of doing participatory research in the middle of a pandemic provide important arguments for further amalgamating the PAR philosophy into similar research designs. The onset of the pandemic has led to a further decentering of the researcher and a shift of the focus to the citizen, in this case the local livestock keeper, that made it more participatory in the stricter interpretation of the term. Letting go of controlling both narrative and implementation of the research will be challenging for researchers in many research fields. However, this shift of power and this transformation of research methodologies is inevitable if the research should remain relevant and impactful. Ultimately, the transition into a Covid-19 future and the awareness that similar pandemics could dramatically interrupt our lives any time, will have an impact on how projects are designed and funded. More long-term funding and less pressure on providing immediate results can build community trust and ownership for research at a local level.